2018
DOI: 10.2147/ijn.s155388
|View full text |Cite
|
Sign up to set email alerts
|

Role of Au(NPs) in the enhanced response of Au(NPs)-decorated MWCNT electrochemical biosensor

Abstract: BackgroundThe combination of Au-metallic-NPs and CNTs are a new class of hybrid nanomaterials for the development of electrochemical biosensor. Concentration of Au(nanoparticles [NPs]) in the electrochemical biosensor is crucial for the efficient charge transfer between the Au-NPs-MWCNTs modified electrode and electrolytic solution.MethodsIn this work, the charge transfer kinetics in the glassy carbon electrode (GCE) modified with Au(NPs)–multiwalled carbon nanotube (MWCNT) nanohybrid with varied concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 61 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Additionally, the CNTs/GCEand Au@CNTs/GCE comparisons demonstrate how Au nanostructures enhance catalytic activity, and the mixture of Au NPs and CNTs has produced a new category of hybrid nanostructures with effective ionic diffusion, that also led to an increase in charge transport due to the formation of globular diffusion regions from around electrode materials. 18 Additional research was done to assess the stability of the electrodes' response to the additional PNS. First and 40th DPV curve for the GCE,CNTs/GCE, Au@CNTs/GCE, and Au-PPy NPs@CNTs within 0.1M PBS containing 5µM PNS are shown in Figure 3 at scan rates of 10mV/s and potential ranges of -0.1 to 0.5V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the CNTs/GCEand Au@CNTs/GCE comparisons demonstrate how Au nanostructures enhance catalytic activity, and the mixture of Au NPs and CNTs has produced a new category of hybrid nanostructures with effective ionic diffusion, that also led to an increase in charge transport due to the formation of globular diffusion regions from around electrode materials. 18 Additional research was done to assess the stability of the electrodes' response to the additional PNS. First and 40th DPV curve for the GCE,CNTs/GCE, Au@CNTs/GCE, and Au-PPy NPs@CNTs within 0.1M PBS containing 5µM PNS are shown in Figure 3 at scan rates of 10mV/s and potential ranges of -0.1 to 0.5V, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, taking into account the effect of the concentration of Au solution on the composition of the MWCNT complex, Mehmood et al [ 101 ] studied the charge transfer kinetics in the GCE modified with AuNP-MWCNT nanohybrid at varied concentrations of AuNPs in the range of 40–100 nM. The results of cyclic voltammetry and EIS demonstrated that the diffusion control, charge transfer mechanism, and concentration of AuNPs are critical factors for the charge transfer rate.…”
Section: Recent Developments In Cnt-based Nonenzymatic Glucose Sensorsmentioning
confidence: 99%
“…Metal nanostructures are generally defined as isolable particles between 1 and 50 nm in size, usually protected within shells to avoid agglomeration. Such nanoparticles have physical, electronic, and chemical properties different from bulk metals due to their small size [43]. Metallic nanostructures (MNS) (e.g., Au, Pt, Cu, Ir, Zn, Ag, Fe, Pd, and their different alloys) have been used in electrochemical biosensing devices to improve their conductive properties [29,33,44] as mediators of the signal from target-bioreceptor recognition [45] and to promote a better contact between bioreceptors and transducers, thus improving the sensitivity of the resultant devices.…”
Section: Metallic Nanostructuresmentioning
confidence: 99%